Effect of arm-ergometry versus treadmill supervised exercise on health-related quality of life and mental health in patients with peripheral artery disease: secondary outcomes from the ARMEX trial - Sandra Magalhães; Mário Santos; Sofia Viamonte; Fernando Ribeiro; Joana Martins; Cristine Schmidt; Henrique Cyrne-Carvalho (Journal of Patient-Reported Outcomes)
Abstract Background Peripheral artery disease (PAD) negatively affects walking performance, health-related quality of life (HRQoL) and mental health. Exercise training is recommended as a first-line treatment for PAD, with potential impact on all these outcomes, but the optimal program design is not completely ascertained. The aim of this study was to compare arm-ergometry (AEx) and treadmill supervised exercise training (TEx) on HRQoL and mental health in patients with PAD. Methods This was an ancillary study of the ARMEX trial, a single-center, single-blinded, parallel group, randomized clinical trial, enrolling symptomatic PAD patients referred to a cardiovascular rehabilitation program (CRP). Participants were randomized (1:1) to a 12-week AEx or TEx, along with the core components of a CRP (nutritional and psychological support). Participants completed the short form 36 Health Survey and the Hospital Anxiety and Depression scale before and after the intervention. Differences between groups in the change from baseline to the end of the study were analyzed using ANCOVA, adjusted for baseline values, or the Mann-Whitney U test. Results Fifty-six patients (66 ± 8.4 years; 87.5% male) were included: AEx (n = 28) and TEx (n = 28). Physical functioning, role-physical, bodily-pain, general health, mental health and physical component summary (PCS) significantly improved in AEx group. In the TEx group, physical functioning, role-physical, bodily-pain, vitality, social functioning, role-emotional and PCS significantly improved. Role-physical and role-emotional improved more in TEx, with no between-group differences in the other domains. Changes in PCS were significantly associated with changes in walking distances. Hospital Anxiety and Depression scale scores improved in both groups, without between-group differences. This improvement was associated with self-reported walking distance. Conclusion Both exercise protocols improved HRQoL and mental health in patients with symptomatic PAD, highlighting exercise-based programs as important treatment strategies for this population. Trial registration number ISRCTN54908548 (retrospectively registered).